2004
DOI: 10.1007/s00702-004-0112-4
|View full text |Cite
|
Sign up to set email alerts
|

The outcome of patients with severe head injuries treated with amantadine sulphate

Abstract: In the group of patients with severe brain injuries treated with standard therapy plus amantadine sulphate the outcome GCS was higher and the case fatality rate lower than in the group treated with standard therapy alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
58
0
7

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(68 citation statements)
references
References 4 publications
3
58
0
7
Order By: Relevance
“…This study was also limited by its retrospective design. In addition, this study differed from that of Saniova et al 39 While Saniova et al initiated amantadine therapy 3 days following the injury, Hughes et al 40 did not initiate the drug until approximately 6 weeks after TBI. The duration of treatment also differed.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…This study was also limited by its retrospective design. In addition, this study differed from that of Saniova et al 39 While Saniova et al initiated amantadine therapy 3 days following the injury, Hughes et al 40 did not initiate the drug until approximately 6 weeks after TBI. The duration of treatment also differed.…”
Section: Discussionmentioning
confidence: 86%
“…Therefore, it is possible that the patient's improvement was due to amantadine, spontaneous recovery in the acute period following injury, or a combination of these factors. Saniova et al 39 reported an improvement in outcome GCS scores and mortality in patients receiving amantadine. However, this study was limited by its small patient population and retrospective design, which did not allow for control in the treatments used.…”
Section: Discussionmentioning
confidence: 98%
“…53,64 In addition to its actions as a dopamine agonist, amantadine is also thought to act as a direct NMDA receptor antagonist, which may reduce glutamate-induced excitotoxicity and associated brain swelling after TBI. 82,83 Thus, early treatment with amantadine may improve arousal by simultaneously minimizing disruptions to dopamine levels in the brain and by reducing excitotoxicity and associated brain swelling.…”
Section: Discussionmentioning
confidence: 99%
“…fluoxetine, amitriptyline, sertraline) [19][20][21], dopaminergic (e.g. methylphenidate, amantadine) [22,23] and cholinergic agents (e.g. donepezil, physostigmine-lecithin combination treatment) [ [24][25][26][27].…”
Section: Discussionmentioning
confidence: 99%